Peningkatan Kualitas Produk Ransel Menggunakan Metode Six Sigma - Ayu Dhilla Nurkamilah; Puti Renosori; Asep Nana Rukmana (UNISBA Press, 2024)
Abstract. Koperasi Penjahit dan Pengrajin Tas is an organization that focuses on producing various types of bags consisting of backpacks, waist bags, tote bags, and chest bags, located in the regency of Garut, the province of West Java. The problem faced by the company is related to the number of defective products that exceed the company's provisions, which is 5.8%. Backpack products are the products with the highest defective products, which is 8.1%. Improvement activities in the production process need to be carried out by the cooperative to reduce the number of defective products by improving quality. In this study, the Six Sigma method was used to reduce the number of product defects by reducing the variations in the process using the Define, Measure, Analyze, Improve, Control (DMAIC) stages. Based on the background that has been described, the formulation of the problem in this study is as follows: